(untitled) (TAJ: Journal of Teachers Association, 2022)
Background: Recent studies have shown that mast cells play an important role in the pathogenesis of irritable bowel syndrome as they release variable mediators which alter enteric nerve and smooth muscle function. The aim of this study was to determine whether mucosal mast cells were increased in the colonic mucosa of IBS patients compared to controls. Materials and Methods: This case-control study was conducted in the Department of Gastroenterology, Bangabandhu Sheikh Mujib Medical University, Dhaka, during the period from April 2016 to March 2017 on cases of IBS and comparison group. We recruited 25 IBS patients and 25 healthy controls for this study. Colonoscopic biopsy was taken from the caecum, ascending colon, descending colon, and rectum. Tissue was stained with Giemsa, and then quantitative evaluation of mast cells was performed. Mast cells counts were compared between the two groups of patients. Results: Mast cells were significantly higher in the caecum, ascending colon, descending colon, and rectum in all subtypes of IBS patients compared to control (10.40±2.10, 6.76±1.83, 8.08±2.19, and 9.16±2.46 vs. 4.20±1.01, 3.32±0.69, 3.04±0.84, and 3.84±1.07 per HPF, respectively). Among four sites, mast cells were significantly higher in the caecum in IBS patients. Mucosal mast cells were relatively elevated in IBS-D patients compared to IBS-C and IBS-M patients, but this was not statistically significant. Conclusion: Mast cells were significantly increased in the caecum, ascending colon, descending colon, and rectum of the patients with IBS compared to controls. These findings suggest that mast cells may play an essential role in the pathogenesis of IBS. TAJ 2021; 34: No-2: 09-14